Development of business performance indicators framework for small and medium enterprises using Delphi-MCDM technique - Nor Mahirah, Mustapha (2019)
The previous Performance Measurement System (PMS) has been seen as a factor to see the success and failure of the company. PMS is known as an important system for developing and maintaining business orientation. It emphasises on the indicator that must be evaluated especially in Small and Medium Enterprises (SMEs). However, success is still difficult to prove in most SMEs when 50% of SMEs are failing to continue business after five years of formation. This is because performance management is not as easy as expected, and SMEs can fail and bankrupt easily. In response to this issue, the objective of this study is to explore performance indicators for SMEs from a different view, that is, from the perspective of business processes. To guide this research effort, a comprehensive research question has been formulated as: how is the performance indicators model to evaluate SMEs performance? Following a review of existing knowledge in the performance measurement literature, a list of twenty-seven related indicators has been proposed with a conceptual research model based on three critical business processes in SMEs, namely strategic management, core function, and support elemental perspectives. This study was carried out in two phases of research inquiry using the mixed method research design. In the first phase, two rounds of Delphi studies have been used to identify the most important performance indicators of SMEs. Then, the Decision Making and Trial Evaluation Laboratory (DEMATEL) technique have been used in the second phase to explore the relationship among those important indicators. Research data has been collected from panels of thirty-seven experts in SMEs consisting of business owners / managers, professional SMEs consultants, and government SMEs officers, and applicable for both phases. The Cronbach’s alpha coefficient for Delphi's study was 0.806, which indicated the high reliability of the instrument. The questionnaires were sent electronically to expert panel members with the response rates of 88% in the first round and 92.3% in the second round of Delphi study, and 38.24% in the DEMATEL techniques. The overall research findings revealed that twenty-one indicators were of importance with five of them were the most critical and driving indicators to improved SMEs performance. In addition, a model called the Performance Measurement Model for SMEs has been developed. The model showed that SMEs in Malaysia should pay full attention to Leadership Proficiency, Competitive Aggressiveness, Marketing Competencies, Time Utilization, and Educational and Training indicators. This model is useful as it can be an ideal tool to guide SMEs to monitor their business towards enhancing long-term success performance. This study is expected to generate new knowledge in performance measurement literature as it evolves the benefits of the business process to SMEs performance. However, the list of practical implementation of performance indicators forwarded by the research is expected to be applicable to various stakeholders within the SMEs only. From a research perspective, the study could stimulate further research activities in the field of PMS and business processes management research.